Detection of Five Types of HPV Genotypes Causing Anogenital Warts (Condyloma Acuminatum) Using PCR-Tm Analysis Technology - Wu, Lixia; Wang, Weifeng; Zhang, Jie; Wu, Xuan; Chen, Yan; Gu, Xiaoping; Shao, Huaqing; Li, Hongsheng; Liu, Weiwei (Frontiers in Microbiology, 2022)
Objectives Condyloma acuminatum (CA) is a common sexually transmitted disease caused by human papillomavirus (HPV) infection. We established a high-throughput, simple, low-cost, and accurate HPV-typing assay (polymerase chain reaction-melting temperature [PCR-Tm] analysis) to detect HPV in CA. Materials and Methods We detected 280 cervical scraping samples, including positive samples of HPV-6 (26), HPV-11 (12), HPV-16 (22), HPV-42 (18), HPV-43 (25), HPV-multiple (19), HPV- other type (58), and HPV-negative samples (100). All samples were compared by PCR-Tm analysis and a flow fluorescence hybridization assay. Sequencing was used to confirm the results of the PCR-Tm analysis. Results PCR-Tm analysis was specific for each genotype (HPV-6, HPV-11, HPV-16, HPV-42, and HPV-43). The sensitivity of the PCR-Tm analysis assay for each genotype was 103, 103, 103, 103, and 102 copies/reaction, respectively. Most of the 158 samples, including 58 HPV-other type positive and 100 HPV-negative samples tested by the flow fluorescence hybridization assay, were tested negative by PCR-Tm analysis. For the 122 remaining samples, 26 HPV-6, 12 HPV-11, 22 HPV-16, 18 HPV-42, 25 HPV-43, and 19 multiple HPV infections were detected through PCR-Tm analysis. In total, 25 HPV-6, 12 HPV-11, 21 HPV-16, 18 HPV-42, 25 HPV-43, and only 10 multiple HPV infections were detected by the flow fluorescence hybridization assay. The kappa coefficient for the analysis of PCR-Tm analysis and flow fluorescence hybridization assay was 0.940 (P < 0.0001), and the 95% confidence interval of the kappa coefficient was 90.3–97.7%. Conclusion PCR-Tm analysis enabled the detection of HPV-6, HPV-11, HPV-16, HPV-42, and HPV-43, including single and multiple infections.